Retensi karyawan sebagai mediator pengaruh talent management terhadap kinerja karyawan di perusahaan pelayaran nasional - Rifa'i, Dian; Rahayu, Sri; Fitrianty, Rifda (Journal of Management and Digital Business, 2026)
This study aims to analyze the influence of talent management on employee performance in national shipping companies with employee retention as a mediating variable. This study uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (PLS-SEM) method using SmartPLS 3.0. The respondents in this study amounted to 130 employees who were selected through purposive sampling techniques, with the criteria of having worked for at least one year and being directly involved in the company's operational activities. Data processing is carried out through the evaluation stages of measurement models and structural models. The results of the study show that all the hypotheses proposed are accepted. Talent Management has a positive and significant effect on Employee Performance, as well as on Employee Retention. In addition, Employee Retention also has a positive effect on Employee Performance. The indirect effect test proves that Employee Retention mediates the influence of Talent Management on Employee Performance, showing that the more effective the company's talent management, the higher the retention and employee performance rates.